JURIDICAL ANALYSIS OF IMPRISONMENT SENTENCES FOR PERPETRATORS OF EMBEZZLEMENT BY TRUCK DRIVERS (A STUDY OF DECISION NUMBER 288/PID.B/2025/PN SRH) - Leader Binent Manullang; Muhammad Ridwan Lubis (CV. Barokah Publsiher, 2026)
Based on the results of the study, it shows that the process of the crime of embezzlement of cargo by the driver in Decision Number 288 / Pid.B / 2025 / PN Srh began when the victim ordered the Defendant to pick up oil palm shells in Siak Regency, then the Defendant transported 32 tons of oil palm shells and took them to the Patumbak area. However, on the way the defendant sold 10 tons of the shells to an unknown person. The proof of the criminal elements in the crime of embezzlement in Decision Number 288 is correct, namely the proof of the elements has been proven based on evidence of witness testimony, the defendant, and evidence of indications. The legal analysis of the prison sentence against the truck driver who embezzled his cargo in Decision Number 288 is that the defendant was sentenced to 2 years in prison. The sentence is considered to have taken into account the principles of justice and legal effectiveness